2019
DOI: 10.1111/lasr.12398
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice Appeals in a Civil Law System: Do Administrative and Civil Courts Award Noneconomic Damages Differently?

Abstract: How do courts award noneconomic damages? Does it matter if the state is the defendant? This article addresses these questions in the context of medical malpractice appeals to the Spanish Supreme Court. Moreover, this study provides the first empirical analysis of the quantification of noneconomic damages in medical malpractice cases in administrative courts, where the state is the defendant, and in civil courts. This separation of jurisdictions is a common feature in civil law tradition countries. Yet, critics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Civil-law-based countries separate the administrative and civil jurisdictions (Amaral-García, 2019a). For this reason, we only incorporate rulings from the Administrative Section of the Supreme Court (the so-called recursos contencioso-administrativos in Spain) in which the Spanish government is either the defendant or the plaintiff, being the firm the other party.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Civil-law-based countries separate the administrative and civil jurisdictions (Amaral-García, 2019a). For this reason, we only incorporate rulings from the Administrative Section of the Supreme Court (the so-called recursos contencioso-administrativos in Spain) in which the Spanish government is either the defendant or the plaintiff, being the firm the other party.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, litigating in the Supreme Court may not only allow firms to take advantage of gray areas but also to change regulations in their favor when this court’s opinion and interpretation of the law agrees with them. Another advantage of using Supreme Court rulings is better data access compared to those in lower courts because all rulings are available in a single and open database (Amaral-García, 2019a) [6].…”
Section: Methodsmentioning
confidence: 99%
“…Civil and commercial law mainly includes four research directions: civil law, commercial law, intellectual property law, marriage and family law, and social law [1]. Civil and commercial law contains two aspects of research: one is civil law, and the other is commercial law [2]. The research and development of civil and commercial jurisprudence plays an important role in the drafting and formulation of China's civil law, which can effectively promote the construction of the rule of law and the development process of the market economy in China.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a recent research it was found that administrative and civil courts do not differ in the awards for non‐economic damages in medical malpractice appeals. See Amalia‐Garcia (2019).…”
mentioning
confidence: 99%